HASHIMOTO’S THYROIDITIS WITH SYSTEMIC INVOLVEMENT: A CASE REPORT - Tang, Jia Jian; Lee, Qiao Yun; Hamizi, Nur Syafiqah; Samingan, Nurshadia; Zaini, Azriyanti Anuar; Jalaludin, Muhammad Yazid (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION/BACKGROUND Hashimoto’s thyroiditis is the most common cause of acquired primary hypothyroidism in children. It is an autoimmune disease involving cell and antibody-mediated immune processes, leading to progressive fibrosis. Severe hypothyroidism may have variable clinical manifestation mimicking other multiorgan dysfunction. CASE We report an 8-year-old male who presented to our centre with a 4-month history of intermittent facial and lower limb swelling associated with unintentional weight gain, cold intolerance, easy fatigability, and regression in school performance. There was no family history of thyroid disease or autoimmune disorder. He visited the healthcare clinic 2 weeks prior to presentation for an upper respiratory tract infection however hypothyroid symptoms were not addressed. He was a short male with weight of 29.7 kg (75th centile) and height of 119 cm (10th centile) with evidence of faltering growth and coarse facies. He has a diffuse goitre measuring 8 x 3 cm (length x width) associated with thyroid acropachy, bilateral pretibial myxoedema and bradyarrhythmia (mean heart rate 56/ min). His biochemical results showed a markedly elevated TSH 2233 mIU/L with FT4 2pmol/L, anti TPO >1000 IU/ml and anti-TG antibody 53.7 IU/ml. He was started with oral levothyroxine 25 mcg daily (0.8 mcg/kg/day) and the dose was titrated up slowly to 50 mcg daily (1.7 mcg/kg/day) over 4 weeks. He received one stress dose of intravenous hydrocortisone 100 mg (100 mg/m2/dose) on the day of admission due to hypotension upon starting thyroxine. His status of adrenal insufficiency has not been ruled out. There were no other complications of myxoedema coma. CONCLUSION We report a case of missed hypothyroidism despite frank symptoms and signs. This was the highest TSH reported in our centre and likely in Malaysia. Prolonged untreated Hashimoto’s thyroiditis is associated with high morbidity and mortality risk. Initiating treatment must be done cautiously to prevent crisis and complications.